The Impact of HDI, Labor Force Participation Rate, Investment, and Technology on Gross Regional Domestic Product in Kalimantan Island - Nikmatun; Hutabarat (RISK : Jurnal Riset Bisnis dan Ekonomi, 2026)
Economic growth is a key long-term development issue that contributes significantly to the sustainability of regional development, particularly in Kalimantan Island as the third-largest contributor to Indonesia’s economy. The relocation of the National Capital (IKN) from Java Island to Kalimantan is viewed as a strategic effort to create a new center of economic growth outside Java in order to reduce interregional economic disparities. This study aims to examine the effects of the Human Development Index (HDI), Labor Force Participation Rate (LFPR), investment, and technology on Gross Regional Domestic Product (GRDP) across five provinces in Kalimantan during the period 2018–2024. Panel data regression is employed as the analytical method. The results indicate that HDI and technology have negative and statistically insignificant effects on GRDP, while investment and LFPR have positive and statistically significant effects during the study period. These findings highlight the importance of improving human resource quality and optimizing technological advancement to enhance labor productivity, which in turn supports economic growth and public welfare. Economic growth can be achieved by strengthening human capital through improved access to education and healthcare. Furthermore, investment productivity should be enhanced through collaboration between the government and business actors by providing fiscal incentives, such as tax relief and capital support, particularly for the manufacturing and technology sectors, to promote more balanced and sustainable economic growth in Kalimantan.